The role of the Dutch Reformed Church mission in the development of nursing in Nyasaland (Malawi) from 1860 to 1927 - Smit, J. J. M (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Nursing) -- University of Stellenbosch, 1986.